2012
DOI: 10.1126/science.1207615
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Can Induce PTSD-Like Memory Impairments in Mice

Abstract: Posttraumatic stress disorder (PTSD) is characterized by a hypermnesia of the trauma and by a memory impairment that decreases the ability to restrict fear to the appropriate context. Infusion of glucocorticoids in the hippocampus after fear conditioning induces PTSD-like memory impairments and an altered pattern of neural activation in the hippocampal-amygdalar circuit. Mice become unable to identify the context as the correct predictor of the threat and show fear responses to a discrete cue not predicting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
229
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(265 citation statements)
references
References 31 publications
30
229
6
Order By: Relevance
“…Much like exposure therapy is applied to PTSD patients in the clinic, this phenomenon is commonly modeled in rodents using fear extinction (Kaouane et al, 2012;McGuire et al, 2010;Rau et al, 2005). Consistent with our data showing more severe PTSD symptoms in E2+ veterans, we confirmed deficits in fear extinction in E2/E2 mice (Olsen et al, 2012), suggesting that an abnormal processing of fear memory may underlie the apparent sensitivity of E2+ individuals to trauma.…”
Section: Discussionsupporting
confidence: 88%
“…Much like exposure therapy is applied to PTSD patients in the clinic, this phenomenon is commonly modeled in rodents using fear extinction (Kaouane et al, 2012;McGuire et al, 2010;Rau et al, 2005). Consistent with our data showing more severe PTSD symptoms in E2+ veterans, we confirmed deficits in fear extinction in E2/E2 mice (Olsen et al, 2012), suggesting that an abnormal processing of fear memory may underlie the apparent sensitivity of E2+ individuals to trauma.…”
Section: Discussionsupporting
confidence: 88%
“…The three gray-gradient arrows represent mild, moderate, and severe stress. Recently, intra-hippocampal infusion of CORT has been shown to induce PTSD-like memory impairment; i.e., low levels of freezing to a shock-predicting context, but high levels of freezing to a nonshock-predicting discrete cue (Kaouane et al 2012), implicating glucocorticoids in mediating detrimental effects of stress. CORT has also been shown to interact with catecholamines in the basolateral amygdala to intensify long-term memory consolidation of emotional events .…”
Section: Glucocorticoid Hypothesis Of Stress: Compatible and Incompatmentioning
confidence: 99%
“…Kaouane et al (2012) have recently shown that infusion of glucocorticoids-which are secreted naturally in response to stressors-directly into the dorsal hippocampus both impairs the processing of memory and results in generalized fear memory and hyperreactive amygdala activity that also typically characterizes PTSD. Further, stressors also result in methylation of the Bdnf gene and decreased BDNF gene expression in the dorsal hippocampus (Kozlovsky et al, 2007;Roth et al, 2011).…”
Section: A Default-mode Network-based Posterior Hippocampus Circuitrymentioning
confidence: 99%